Games children play II games to develop social skills, teamwork, balance and coordination - Payne, Kim John M.ED; Waletzko, Cory (Hawthorn Press, 2021)
Games children play II is a tried and tested collection of 237 games for groups, classes, families and communities to enjoy playing. Kim John payne and Cory Waletzko link playing games with child development, giving the "Why?" not just the "What?" and "How?". It highlights how to help children who have difficulty playing. Educators, parents, outdoor activity leaders and youth workers will find this a must-have resource. Here are games for developing movement, co-operation, fairness and equity for 7 to 10-year-olds and games for courage, accuracy, teamwork and gentle preparation for sports for 11 to 12-year-olds. Games for renewing playground culture and holding a DIY Olympic Games. There are sections on child development, introducing game sessions, children's temperaments, nurturing the senses and teaching movement to children.